Correction of Midface Depression Using an Inverted m-shaped Expanded Polytetrafluoroethylene Implant Improves Gingival Exposure. Issue 6 (December 2016) - Wei, Jiao; Herrler, Tanja; Xu, Hua; Deng, Ning; Li, Shiyu; Li, Qingfeng; Dai, Chuanchang
Abstract : Background: Current approaches for the treatment of gingival exposure are often time- and cost-consuming and/or rather invasive. We previously observed a strong correlation between the presence of gingival excess and midfacial depression and here propose an easy 1-step correction technique as a new strategy to improve gingival exposure. Method: From February 2004 to December 2012, 42 patients with gingival exposure associated with different degrees of midfacial depression, defined by Frankfort horizontal plane-labrale superius-subspinale angle and sella-nasion-A point angle, were treated by implantation of an inverted m-shaped expanded polytetrafluoroethylene at the base of the piriform aperture in a subperiosteal location. Patient pictures were taken preoperatively and postoperatively to assess gingival exposure at rest and fullest smile, as well as measurements of upper lip length, nasolabial angle, and facial convexity angle. A postoperative patient satisfaction survey was performed. Results: The average maximum gingival exposure was 5.52 ± 1.64 mm preoperatively and significantly decreased to 1.79 ± 0.67 mm at 6 months after surgery ( P < 0.05) along with a significantly improved nasolabial angle from initially 85.3° ± 6.21° to 95.2° ± 7.1° ( P < 0.05). The majority of patients (90.5%) rated their postoperative outcome as highly improved and improved. Temporary discomfort involving upper lip numbness, foreign body sensation, and stiff smiling expression was complained at 1 month postoperatively and gradually returned to normal after 3 months. No late recurrence or other complications were seen in any of the patients. Conclusions: For cases involving midface depression, the present technique provides an effective and permanent treatment strategy to improve excessive gingival exposure. This single-step approach is a safe and technically easy therapeutic option which is associated with high patient acceptance.